DEVELOPMENT OF A GREEN ECONOMY ON THE BASIS OF SOCIAL RESPONSIBILITY (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In modern conditions, the development of a green economy is becoming one of the priority areas of modern global development, aimed at ensuring sustainable economic growth taking into account environmental constraints. The integration of the principles of social responsibility into the economic activities of enterprises creates the prerequisites for a harmonious combination of economic, social and environmental interests. All this requires in-depth research into the main aspects of the formation of a green economy on the principles of social responsibility, as well as identifying ways to increase the effectiveness of its implementation in business practice.The purpose of the article. The purpose of the study is to identify key mechanisms for integrating the principles of social responsibility into the business processes of enterprises, assess their effectiveness for economic and environmental development to ensure a harmonious balance between socio-economic goals and the preservation of ecosystems.Methods. The research process used an interdisciplinary approach, which includes an analysis of the theoretical foundations of the green economy and social responsibility, as well as approaches to their implementation. Systems analysis methods were used to assess the relationships between economic, social and environmental components, as well as comparative analysis to study international experience in implementing the green economy. Empirical methods were used to identify current problems and prospects for business development in the context of a socially responsible approach.Results. The article examines the role of social responsibility as a fundamental basis of a green economy, which contributes to the harmonious combination of economic, environmental and social interests. The mechanisms of integrating the principles of social responsibility into business processes are analyzed, which include the introduction of environmentally friendly technologies, the reduction of harmful emissions and the rationalization of resource use in economic processes. The need to implement a strategy of socially responsible development in the activities of business entities is proven to ensure business competitiveness and promote environmentally safe conduct of economic activity. Social responsibility is defined as a functional tool for achieving sustainable economic progress and environmental protection. An organizational and economic mechanism for the functioning of a green economy based on social responsibility is formed.Conclusions. It has been proven that the development of a green economy based on social responsibility is an important tool for ensuring sustainable economic growth that takes into account the environmental and social needs of society. It has been determined that the integration of these principles into the activities of enterprises contributes to increasing competitiveness, preserving natural resources, and forming a positive social reputation of business.
Keywords: green economy, greening of business processes, social responsibility, sustainable development, green technologies.